2020
DOI: 10.1038/s41598-020-60098-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism underlying starvation-dependent modulation of olfactory behavior in Drosophila larva

Abstract: Starvation enhances olfactory sensitivity that encourage animals to search for food. the molecular mechanisms that enable sensory neurons to remain flexible and adapt to a particular internal state remain poorly understood. Here, we study the roles of GABA and insulin signaling in starvationdependent modulation of olfactory sensory neuron (oSn) function in the Drosophila larva. We show that GABA B-receptor and insulin-receptor play important roles during oSn modulation. Using an OSN-specific gene expression an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 61 publications
2
18
1
Order By: Relevance
“…Whereas it has been demonstrated that the olfactory plasticity observed in fasted animals results from enhanced presynaptic activity in the antennal lobes mediated via the short neuropeptide F [22] and possibly insulin and GABA signaling [23], we show here that the nutritional status clearly impacts peri-receptor events in the olfactory detection process.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Whereas it has been demonstrated that the olfactory plasticity observed in fasted animals results from enhanced presynaptic activity in the antennal lobes mediated via the short neuropeptide F [22] and possibly insulin and GABA signaling [23], we show here that the nutritional status clearly impacts peri-receptor events in the olfactory detection process.…”
Section: Discussioncontrasting
confidence: 72%
“…In this later study, starvation was shown to increase sNPF receptor signaling, which in turn enhanced presynaptic activity in Drosophila olfactory neurons. It has also been shown that insulin signaling interacts with GABA signaling to impact ORN function upon starvation in Drosophila [ 23 ], potentially impacting the expression of downstream genes. Thus, modulation of the peripheral olfactory activity makes an important contribution to food search behavior in response to starvation.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, highest density of central insulin receptors and highest concentration of insulin in mammalian brain are found in the olfactory bulb (Havrankova et al, 1981). Insulin signaling plays a significant role in satiety-dependent modulation of smell sensitivities (Bargmann, 2012;Taghert and Nitabach, 2012;Ko et al, 2015;Slankster et al, 2020). Like ACE2, insulin receptors are expressed on surface of both OSNs and glia (Nassel et al, 2013;Musashe et al, 2016).…”
Section: Searching For Insights In the Nosementioning
confidence: 99%
“…The most straightforward way is to elicit changes in sensitivity and attractiveness to specific food-related cues. Important examples of this phenomenon have been described in both the olfactory system (Ko et al, 2015;Lin et al, 2019;Root et al, 2011;Sayin et al, 2019;Slankster et al, 2020), and the gustatory system of flies (Inagaki et al, 2012;Jaeger et al, 2018;LeDue et al, 2016;Musso et al, 2019). In taste, a particular area of focus has been sugar detection.…”
Section: Introductionmentioning
confidence: 99%